All Souls’ Day in the Village of Ladovica - Then and Now - Miljković, Marija D. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper is based on the field research in the area of Ladovica village, Vlasotince Municipality. The subject of this research is a Serbian custom which refers to paying respects to the souls of the deceased – All Souls' Day, the aim of which is to determine the differences that occurred in time by comparison. Respondents, the residents of this village, talk about customs related to All Souls' Day, remembering the past. They testify that Ladovica village did not allow the customs used by their ancestor, which they spread to their descendants now, to fall into oblivion. Family members of the deceased in this village continue to respect certain rituals, whereby, in their belief, they are provide with fertility, peace, and life, which in many situations depends on their ancestors. However, it turned out that some customs were modifie; namely, the inhabitants unconsciously accepted new trends imposed by modern life.
Keywords: present; past; beliefs; custom; All Souls' Day; village Ladovica